(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
هدفت هذه الدراسة إلى تدريج اختبار القدرات المعرفية (البطارية التمهيدية) باستخدام نموذج راش أحادي المعلم, إضافة إلى عمل المعايير المختلفة التي تفسر القدرات المختلفة للأفراد وقد تم تطبيق الاختبار على عينة من أطفال رياض الأطفال وتلاميذ الصف الأول والثاني من مدارس محافظة اللاذقية بلغ عددها (1081) تلميذاً وتلميذة واستخدم برنامج الspss وبرنامج الwinsteps لإجراء المعالجات الإحصائية اللازمة وفقاً لنموذج راش, وتوصلت نتائج الدراسة إلى حذف (38) بنداً من بنود اختبار القدرات المعرفية ليبلغ عدد بنود الاختبار بعد تدريجه باستخدام نموذج راش0(172), وإلى التحقق من صدق وثبات هذا الاختبار بعد تدريجه,وإلى عمل المعايير المختلفة من رتب مئينية ,و درجات تائية, ونسب ذكاء انحرافية مقابلة للتقديرات المختلفة للأفراد. This study aimed at arranging the items of cognitive abilities test (primary battery) by using Rash s one parameter model , In addition ,different forms for interpreting the individuals level of ability were carried out. The test was conducted on a sample of (1081) students from Lattakia schools and kindergarten . using "SPSS" program and Winsteps for statistical treatment in accordance with Rasch Model. The results showed the necessity of omitting (38) items of cognitive abilities test because they were not fitting the model. The remain items that were left were (172). And proved the validity and the reliability of the test. Moreover, the present study form criteria for percentiles rank, T scores, and standardized intelligent quiescent that equal for the different individual ability.